1986
DOI: 10.1111/j.1348-0421.1986.tb00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of T Cell‐Mediated Immunity to Listeria monocytogenes in Pregnant Mice

Abstract: In order to study pregnancy-induced changes in cell-mediated immunity to Listeria monocytogenes, acquired resistance and T cell functions in pregnant mice were compared with those in nonpregnant mice after immunization with viable listerial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This diminution in immunoreactivity helps protect the fetus from rejection (31, 33) but increases maternal susceptibility to infection by pathogens such as listeria (24,35). Previous studies established that CpG ODN stimulate the innate immune system of normal adult animals, thereby improving host resistance to infection by a variety of bacterial, viral, and parasitic pathogens (6,7,15,19,23,27,29,30,32,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This diminution in immunoreactivity helps protect the fetus from rejection (31, 33) but increases maternal susceptibility to infection by pathogens such as listeria (24,35). Previous studies established that CpG ODN stimulate the innate immune system of normal adult animals, thereby improving host resistance to infection by a variety of bacterial, viral, and parasitic pathogens (6,7,15,19,23,27,29,30,32,42).…”
Section: Discussionmentioning
confidence: 99%
“…This immunosuppressed state prevents maternal rejection of the fetus (31,33) but has the unfortunate consequence of increasing maternal susceptibility to certain infectious agents (24,35).…”
mentioning
confidence: 99%
“…Although granulocytes, macrophages as well as CD4+ and CD8+ T cells were recruited to the liver, these cell populations were unable to restrict growth of L. monocytogenes. In vitro studies have revealed that supernatant from spleen cells of pregnant mice stimulated with L. monocytogenes antigen failed to stimulate macrophages for an appropriate killing of tumor cells [44]. In addition, Sano et al [44] noticed reduced T-cell responses in Listeria-infected pregnant mice as evidenced by a lower delayed-type hypersensitivity (DTH) reaction than in virgin animals.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies have revealed that supernatant from spleen cells of pregnant mice stimulated with L. monocytogenes antigen failed to stimulate macrophages for an appropriate killing of tumor cells [44]. In addition, Sano et al [44] noticed reduced T-cell responses in Listeria-infected pregnant mice as evidenced by a lower delayed-type hypersensitivity (DTH) reaction than in virgin animals. These impaired cellular immune responses in pregnant mice may be explained by our observation of a reduced expression of TNF, IFN-γ, IL12p40, and iNOS in liver and of IFN-γ in serum, which are all of key importance for an effective control and elimination of L. monocytogenes [3,5,13,18,19,20,25,43].…”
Section: Discussionmentioning
confidence: 98%
“…Pregnancy leads to a generalized suppression of the adaptive immune system, typified by significantly decreased cell-mediated immunity and reduced Th1 responsiveness [21,33,34], and this immunosuppressed state prevents maternal rejection of the fetus but has the unfortunate consequence of increasing maternal susceptibility to certain infectious agents [16,23]. This is considered to be the reason that pregnant IFN-γ knockout mice died more rapidly due to B. abortus infection than non-pregnant IFN-γ knockout mice.…”
Section: Discussionmentioning
confidence: 99%